Physicochemical Properties of Pueraria Root Starches and Their Effect on the Improvement of Buckwheat Noodle Quality. Issue 3 (14th November 2016) - Liang, Jie; Maeda, Tomoko; Tao, Xiang‐Lin; Wu, Yue‐Hui; Tang, Han‐Jun
Abstract : The physicochemical properties of starches from cultivated Pueraria thomsonii Benth were examined and compared with those of P. lobata (Willd.) Ohwi and other root starches, and the effect of pueraria root starches on the improvement of buckwheat noodle quality was investigated. The total content of isoflavones in P. thomsonii root starches was higher than in P. lobata root starches, and the size and uniformity of those particles displayed a significant difference. The gel stabilities of pueraria root starches were similar and more favorable than those of potato starch and sweet potato starch. For the amylose molecular properties of pueraria root starches, the λmax and blue value index were higher than those of the potato starch and the sweet potato starch, whereas the amylose content and degree of polymerization were much lower in comparison. However, amylopectin branch lengths of pueraria root starches were shorter. Thus, pueraria root starches could improve the quality of buckwheat noodles and enhance their nutritional function. Therefore, pueraria root starches may be regarded as raw materials that influence the quality of buckwheat noodles.